PENGARUH DISIPLIN KERJA KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. BAYUS BALI CARGO CABANG KEROBOKAN - Ni Putu Shintya Dewi; Anak Agung Dwi Widyani; Ni Made Satya Utami (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
The importance of work discipline and organizational commitment to find out how far the employee's performance is in carrying out the assigned task. This study aims to determine the effect of work discipline on employee performance, organizational commitment to employee performance, work discipline, and organizational commitment to employee performance at PT. Bayus Bali Cargo Kerobokan Branch. The population in this study were all employees of PT. Bayus Bali Cargo Kerobokan Branch. The population in this study were all employees of PT. The number of Bayus Bali Cargo at Kerobokan Branch is 34 people. The sample is determined using the census method. Research data collection was carried out by observation, interviews and questionnaires. Data were analyzed using multiple linear regression analysis techniques to answer the problem formulation with the help of the Statistical Product and Service Solutions (SPSS) program. The results of testing the hypothesis show that the variable work discipline has a positive and significant effect on employee performance, organizational commitment has a positive and significant effect on employee performance, and work discipline, and organizational commitment simultaneously affects employee performance.